Euglycemic Ketoacidosis as a Complication of SGLT2 Inhibitor Therapy - Palmer, Biff F; Clegg, Deborah J (Clinical journal of the American Society of Nephrology, 2021)
Sodium-glucose cotransporter-2 (SGLT2) inhibitors are drugs designed to lower plasma glucose concentration by inhibiting Na -glucose-coupled transport in the proximal tubule. Clinical trials demonstrate these drugs have favorable effects on cardiovascular outcomes to include slowing the progression of CKD. Although most patients tolerate these drugs, a potential complication is development of ketoacidosis, often with a normal or only a minimally elevated plasma glucose concentration. Inhibition of sodium-glucose cotransporter-2 in the proximal tubule alters kidney ATP turnover so that filtered ketoacids are preferentially excreted as Na or K salts, leading to indirect loss of bicarbonate from the body and systemic acidosis under conditions of increased ketogenesis. Risk factors include reductions in insulin dose, increased insulin demand, metabolic stress, low carbohydrate intake, women, and latent autoimmune diabetes of adulthood. The lack of hyperglycemia and nonspecific symptoms of ketoacidosis can lead to delays in diagnosis. Treatment strategies and various precautions are discussed that can decrease the likelihood of this complication.